Pulmonary Complications in Diabetes Mellitus: The Role of Glycemic Control - Ardigo, Diego; Valtuena, Silvia; Zavaroni, Ivana; Baroni, Maria C.; Delsignore, Roberto (Current Drug Targets - Inflammation & Allergy, 2004)
Insulin deficiency induces an increase in blood glucose levels that, in long run, becomes toxic for many organs and systems. Microangiopathy and derangements in the immune function are known consequences of hyperglycemia, but the way in which these systemic alterations may affect pulmonary function has been scarcely investigated. Although confirmation from large clinical trials is still to come, the diabetic disease seems to hit the pulmonary microcirculation as any other organ by increasing vessel wall thickness and impairing gas exchange, which leads to a measurable loss of function and respiratory efficiency. In addition, a diabetic lung is more susceptible to low respiratory tract infections by atypical microorganisms and more likely to host severe episodes of pneumonia than a normal, non-diabetic lung. This is a review of current knowledge on the impact of diabetes mellitus in lung health. We have paid special attention to the role of metabolic control in preventing damage to the lung by sustained hyperglycemia.
Keywords: lung function